Texture balancing in a fcc/bcc multilayered composite produced by accumulative roll bonding. (15th January 2017) - Duan, J.Q.; Quadir, M.Z.; Xu, W.; Kong, C.; Ferry, M.
Abstract: The high strain deformation and recrystallization behaviour of a Fe/Ni multilayered composite sheet fabricated by accumulative roll bonding has been investigated. The comparable initial hardness and subsequent strain hardening behaviour of the Ni and Fe layers reduces the flow compatibility related challenges at the bonding interfaces, thereby generating parallel layers of uniform thickness during rolling to true strains up to 4.18. Typical body centred cubic ( α- and γ- fibres) and face centred cubic ( β- fibre) rolling textures were generated in the Fe and Ni layers, respectively. During annealing at 700 °C, recrystallization takes place homogenously in the Ni layers but commences initially by particle stimulated nucleation at oxide debris present at the interface of adjacent Fe layers. After recrystallization, the texture of the Ni layers is similar to the starting material prior to ARB, but considerable texture modification occurs in the Fe layers. For both metals, oriented growth of nucleated grains has the greatest influence on the final annealing textures, which generates the classic Cube texture in Ni and a 511<1 5 10> texture in Fe. While these final textures of the individual Fe and Ni layers are not conducive to good formability, texture-based Schmidt factor calculations of the combined layers show an overall balance in texture components that points to a reduction in planar anisotropy. The ability to fabricate multilayered textured sheets by this route is a promising way of controlling the anisotropy of both strength and ductility. Graphical abstract: Image 1